2004
DOI: 10.14411/eje.2004.079
|View full text |Cite
|
Sign up to set email alerts
|

Carabid beetle occurrence at the edges of oak and beech forests in NW Spain

Abstract: Abstract. We examined the occurrence of carabid beetles (Coleoptera, Carabidae) at the edges of oak (Quercus pyrenaica) and beech (Fagus sylvatica) forests in León, NW Spain. Pitfall traps were used to collect beetles from April to October 2002, and leaf litter cover and depth were measured. Traps were placed at three distances (0, 50 and 100 m) from the edges of eight forest patches. A total of 5436 carabids belonging to 43 species were collected. We found no statistically significant edge effect at the carab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 37 publications
(47 reference statements)
2
26
0
1
Order By: Relevance
“…Typical forest carabid species like C. macrocephalus or Pterostichus cantaber (Chaudoir, 1868) (Taboada et al, 2004), frequently found on heathlands (Cuesta et al, 2008), and most of the harvestmen, which survive best at high humidities (Bragagnolo et al, 2007), are clearly associated with the heather dominated areas. The high records of arthropods in the heather dominated areas might also be due to less trampling and soil compactation in these areas, and the lack of burning in the past might have favoured the presence of vegetation at a more advanced successional stage.…”
Section: Discussionmentioning
confidence: 99%
“…Typical forest carabid species like C. macrocephalus or Pterostichus cantaber (Chaudoir, 1868) (Taboada et al, 2004), frequently found on heathlands (Cuesta et al, 2008), and most of the harvestmen, which survive best at high humidities (Bragagnolo et al, 2007), are clearly associated with the heather dominated areas. The high records of arthropods in the heather dominated areas might also be due to less trampling and soil compactation in these areas, and the lack of burning in the past might have favoured the presence of vegetation at a more advanced successional stage.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of both individuals and species belonging to forest specialist species increased as the cover by leaf litter cover, decaying wood, and herbs as well as prey availability increased. Leaf litter greatly influences the spatial occurrence pattern of carabids (Koivula et al, 1999;Magura et al, 2000Magura et al, , 2004Magura et al, , 2005Taboada et al, 2004). A high cover of leaf litter and decaying wood material indicate an undisturbed forest habitat which is preferred by forest specialists and provides shelter against predators, suitable sites for aestivation, hibernation, egg and larval development.…”
Section: The Impact Of Habitat Characteristics On Carabidsmentioning
confidence: 99%
“…Moreover, other typical forest types of the same mountainous area share a high number of carabid species with the Pyrenean oak forest: pine (31 of 50 collected species in common, Taboada et al, unpubl. ) and beech (13 of 19 species in common, Taboada et al, 2004). For example, Cryobius cantabricus and N. asturiensis, both forest specialist species, are endemic to the Cantabrian mountain range, but are found in all three forest types.…”
Section: 2mentioning
confidence: 99%